A CORRELATION STUDY BETWEEN TRANSCUTANEOUS BILIRUBIN AND TOTAL SERUM BILIRUBIN LEVELS AMONG NEONATES - SHARMA, ABHISHEK KUMAR; DHAWAN, KAPIL; MAKKAR, MEENAL; SHARMA, RUCHIRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The availability of modern bilirubin meters that measure bilirubin concentration in dermal and subcutaneous tissues has made it possible to obtain serial, non-invasive (i.e., painless) TcB (transcutaneous bilirubin) measurements. However, concerns have been raised regarding the appropriateness of comparing these TcB values to serum bilirubin values. This study aims to find a correlation between transcutaneous bilirubin and total serum bilirubin. Methods: Prospective analytic study carried out in NICU of Govt. RDBP Jaipuria Hospital. Newborn babies up to the 10th postnatal day of life with visually found jaundice had been enrolled in the study. TcB was measured over mid-sternum with Dräger JM 105™ device. Simultaneous total serum bilirubin (TSB) measurements had been done. Pearson’s correlation coefficient and Bland–Altman analysis had been done. ROC curves of mean TcB at different TSB level had been constructed. Results: In the study, 120 babies had been included. A significant correlation was founded between TcB and TSB measured values. Pearson’s correlation coefficient was 0.892 (p<0.001). The average error in evaluating hyperbilirubinemia with TcB compared to TSB was 0.101, with limits of agreement between −3.73 and +3.55. The AUOC at three TSB levels (>10 mg/dl, >12 mg/dl, and >15 mg/dl) was 0.860, 0.892, and 0.849. Conclusion: In our study, TcB measurements correlated well with TSB measurements and validated its use as a screening tool for the evaluation of jaundice in newborns.